2023
DOI: 10.1021/acscatal.2c05129
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Precise Dinuclear Ni2 Active Site-Modified MOF-Derived ZnO@NC Heterojunction toward High-Performance N2 Photofixation

Abstract: The development of heterogeneous catalysts with atom-dispersed active sites is essential to facilitate nitrogen (N2) activation for the N2 reduction reaction (NRR). However, it remains a major challenge to tune the coordination configuration of the metal centers to further accelerate the activation kinetics. Herein, an atomically precise dinuclear Ni2 site-modified metal–organic framework (MOF)-derived ZnO@NC heterojunction (ZnO@NC-Ni2) was developed for effective N2 photofixation under mild conditions. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Generally speaking, the higher the photocurrent intensity of a photocatalyst, the better its photocatalytic carrier separation efficiency. 59,60…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, the higher the photocurrent intensity of a photocatalyst, the better its photocatalytic carrier separation efficiency. 59,60…”
Section: Resultsmentioning
confidence: 99%
“…Generally speaking, the higher the photocurrent intensity of a photocatalyst, the better its photocatalytic carrier separation efficiency. 59,60 As shown in Fig. 4a, the samples demonstrate a rapid light current response to the periodic light on-off.…”
Section: Photocatalytic Degradation Performancementioning
confidence: 88%
“…Zhang et al designed a ZnO@N-doped carbon heterojunction containing homonuclear diatomic Ni 2 sites (ZnO@NC-Ni 2 ) for the NRR. 166 As illustrated in Fig. 10, the N 2 adsorption mode at the binuclear Ni 2 site was carried out in a side-on bridging adsorption configuration, instead of the terminal adsorption configuration at the mono-metallic Ni 1 site.…”
Section: Applications In Catalysismentioning
confidence: 99%
“…30,31 In the presence of several layers, the coordination in the axial direction may be prohibited and new co-adsorption configurations are presented. 32 Among numerous SACs, graphitic carbon nitride (g-C 3 N 4 ) doped with metal atoms (M@g-C 3 N 4 ) stands out for exceptional NRR performance, 6,33 because g-C 3 N 4 has many inherent advantages, such as providing abundant anchoring sites to capture metal atoms and maintaining the noble metal atoms in their neutral state. 34 aqueous solution can be simultaneously captured.…”
mentioning
confidence: 99%
“…Furthermore, recent works have also suggested that the possibility of multiadsorption of surface species, such as *OH, *N 2 , and *H 2 O, on SACs, which makes the consideration of possible co-adsorption configurations of reactants and environmental species important for evaluation of the catalytic performance of designed SACs. However, under real reaction conditions with specific applied electrode potentials and pH values, the stability of the expected co-adsorption configurations of functional ligands exhibiting high NRR catalytic performance has rarely been considered in the design of SACs. Furthermore, for the widely used 2D substrates, the layers of the substrate are difficult to control, and usually, substrates with several layers are prepared. , In the presence of several layers, the coordination in the axial direction may be prohibited and new co-adsorption configurations are presented …”
mentioning
confidence: 99%